2017
DOI: 10.1128/aac.01820-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Ceftazidime-Avibactam against Isolates in a Phase 3 Open-Label Clinical Trial for Complicated Intra-Abdominal and Urinary Tract Infections Caused by Ceftazidime-Nonsusceptible Gram-Negative Pathogens

Abstract: The in vitro activity of ceftazidime-avibactam was evaluated against 341 Gram-negative isolates from 333 patients in a randomized, phase 3 clinical trial of patients with complicated urinary tract or intra-abdominal infections caused by ceftazidime-nonsusceptible pathogens (NCT01644643). Ceftazidime-avibactam MIC 90 values against Enterobacteriaceae and Pseudomonas aeruginosa (including several class B or D enzyme producers that avibactam does not inhibit) were 1 and 64 g/ ml, respectively. Overall, the ceftaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Ceftazidime-avibactam (87.4% susceptible) was the second most potent agent tested against isolates of P. aeruginosa from six Latin American countries in 2012 to 2015, after colistin (94.9% susceptible). Based on the in vitro susceptibilities and proven clinical efficacy (30,31,(38)(39)(40)(41), ceftazidime-avibactam should be considered in the treatment of indicated infections caused by susceptible Enterobacteriaceae and P. aeruginosa strains.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftazidime-avibactam (87.4% susceptible) was the second most potent agent tested against isolates of P. aeruginosa from six Latin American countries in 2012 to 2015, after colistin (94.9% susceptible). Based on the in vitro susceptibilities and proven clinical efficacy (30,31,(38)(39)(40)(41), ceftazidime-avibactam should be considered in the treatment of indicated infections caused by susceptible Enterobacteriaceae and P. aeruginosa strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings were comparable to that of Stone et al who showed that the CAZ and CZA MIC 50/90 values for 27 P. aeruginosa isolates were 64/> 64 and 8/64 , respectively, versus 64/128 and 32/64 in the present study. Higher MIC 90 values were assessed to be due to the possession of either a class B or a class D enzyme as those strains which lacked these enzymes had a MIC 90 value of 8 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…avibactam studies in which baseline pathogen samples were obtained from patients with cIAI and cUTI, including isolates that were nonsusceptible to ceftazidime (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%